The Relationship between Parental Communication in the Family and Their Children’s Confidence in PAUD SPNF SKB Padang Panjang - Listy, Cynthia; Ismaniar, Ismaniar (Universitas Negeri Padang, 2024)
This research is motivated by the low self-esteem of children which is thought to be due to improper communication between parents in the family. This study describes (1) parental communication in the family (2) describing children's self-esteem (3) describing the relationship between parental communication in the family and the self-esteem of PAUD SPNF SKB Padang Panjang children. This study uses aquantitative approach in a relational way were parents whose children attended PAUD SPNF SKB Padang Panjang, totaling 34 people. The sampling technique used simple random sampling of 70% of the population, namely 24 people. instruments data collection the form of a list of statements analysis Data techniques percentages and rank order. The results of this study indicate that (1) parent-parent communication in families with children attending PAUD SPNF SKB Padang Panjang is poor; (2) The self-confidence of PAUD SPNF SKB Patang Panjang children is low. (3) The data of result processing there show that is a relationship significant parental communication in the family and their child's confidence in PAUD SPNF SKB Padang Panjang. Suggestions in this study are that (1) parents pay more attention to how to communicate well, as well as carry out literacy regarding the benefits of good communication; (2) children are still trying to practice courage and self-confidence to be even better; (3) parents pay more attention to how to communicate well with children, because the better the communication delivered, the higher the child's self-confidence.